TEKNOLOGI COAL WATER FUEL (CWF) MENGGUNAKAN BATUBARA KALIMANTAN SELATAN - R. Herry Supriyanto (Badan Pengkajian dan Penerapan Teknologi, 2005)
A study of advantages of using CWF for combustion was carried out. Among of those advantages that could be attained when oil fuel is replaced with CWF (Coal Water Fuel) are, saving highly economical oil fuel and expanding energy diversification. Other advantages are that combustion facilities such as generator, combustion chamber to produced steam and heat will be saved should oil price is no longer affordable. Oil substitution with CWF may beÂ performed when its physical features pushed to proximate or equal to oilâ€™sÂ physical features. Such features may be achieved by crushing the coal to very fine powder (less than 75 micron or 200 mesh) and mixed with water and adding some additive, thus resulting a desired water feature and long-lasting mixture stability.Kata kunci: Coal, air, aditives, CWF, efficient combustion